Influence of environmental parameters on shrimp post-larvae in the Sungai Pulai seagrass beds of Johor Strait, Peninsular Malaysia - Arshad, Aziz; Ara, Roushon; Sarker, S. M. Nurul Amin Harmuj Ali; Effendi, Mulyani; Che Cob, Zaidi; Abd. Ghaffar, Mazlan (Academic Journals, 2011)
Monthly sampling for shrimp post-larvae was conducted between April 2007 and March 2008 from the seagrass beds of Sungai Pulai Estuary, Johor, Peninsular Malaysia. Samples were collected from sub-surface using a bongo net equipped with a flow meter. In situ environmental parameters such as water temperature, dissolved oxygen, pH, salinity, total dissolved solid and conductivity were recorded during each sampling time. Total catch was comprised of four major taxa namely:Lucifer (94.9%), Acetes (1.52%), Penaeus (0.13%) and Mysis (0.06%). Mean density of shrimp post larvae (PL) was calculated as 22,614.74 individuals/100 m3. Peak abundance of Penaeus was found in June to July, while Acetes was found throughout the year with peak abundance in September. Higher abundance ofLucifer compared to the other genus was observed throughout the year with peaks in the monsoon months (May to July and October to December). The occurrence and abundance of Mysis was also restricted only in the monsoon months (November to January and May to July). There were significant correlation between the abundance of shrimp PL and in situ environmental parameters in the study area.